Covid-19 cases influencing the Stock Exchange indices on the example of BIST100 in Turkey, NASDAQ in the USA and WIG in Poland - Bolek, Cezary; Bolek, Monika (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The goal of this paper is to show differences between markets’ reactions to a number of Covid-19 new cases. Stock exchanges and their indices from Turkey, the USA and Poland are analyzed during the first year of the global pandemic. The hypothesis that there are significant differences between markets regarding the reaction to new Covid-19 cases is tested in this research paper. Methodology: BIST100 Index representing the Istanbul Stock Exchange in Turkey, NASDAQ Composite representing NASDAQ Exchange in the USA and WIG Index representing the Warsaw Stock Exchange in Poland are analyzed in relation to Covid-19 new cases. The correlation analysis with delays of markets’ reactions and panel data OLS regression models are tested with rates of return as dependent variables. Results of the research: The findings show the immediate negative influence of new cases rates of change on the stock indices rates of return, although there are some differences and similarities between correlation coefficients, especially when the delays in reactions are taken into consideration. The Turkish exchange was reacting immediately to the rates of change of new Covid-19 cases, the US exchange needed more time to adjust, while in Poland the correction was detected after investors’ over-reaction in the first two weeks. The significant difference between the Polish and US markets regarding the correlation is confirmed indicating that the reactions on the global market were not identical. What the findings add to the literature is the evidence of differences and similarities between markets representing different religions, continents, and cultures.